(untitled) (Experimental biology, 2016)
This article deals with the development of creative abilities of students in teaching biology at school. Using a variety of innovative learning technologies biology teacher should pay special attention to the development of creative abilities provided educational material , as well as the ability to apply in practice . In addition , the teacher should pay special attention to the educational value of learning. Since the main didactic principles when it -training and education - a single process. The study used methods of training such as equations of the method , learning to perform creative tasks , job training literature , problematic search , independent search for information through the Internet, as well as through the library. According to the results of psycho - pedagogical research , we found that the level of job allows students to explore the learning material deep , versatile, and independently analyze draw conclusions. Of the 25 students , 80% of the assigned tasks corrected easily, naturally , and 10 % of students were not able to give the right answers, 5 % of the students are not able to respond to the job. We also consider , in order to develop the self-development of educational materials necessary to conduct lessons gradually complicating the task level .